2022
DOI: 10.1126/science.aaz8777
|View full text |Cite
|
Sign up to set email alerts
|

Trained ILC3 responses promote intestinal defense

Abstract: Group 3 innate lymphoid cells (ILC3s) are innate immune effectors that contribute to host defense. Whether ILC3 functions are stably modified after pathogen encounter is unknown. Here, we assess the impact of a time-restricted enterobacterial challenge to long-term ILC3 activation in mice. We found that intestinal ILC3s persist for months in an activated state after exposure to Citrobacter rodentium . Upon rechallenge, these “trained” ILC3s proliferate, display enhanced interleukin-22 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 41 publications
3
56
0
Order By: Relevance
“…S5 C ). We also showed that PBMCs from controls secreted IFN-γ in response to IL-12, IL-23, and a combination of IL-23 and IL-1β (known to potentiate IL-23; Serafini et al, 2022 ) as determined by multiplex ELISA ( Fig. 7 F ).…”
Section: Resultsmentioning
confidence: 68%
“…S5 C ). We also showed that PBMCs from controls secreted IFN-γ in response to IL-12, IL-23, and a combination of IL-23 and IL-1β (known to potentiate IL-23; Serafini et al, 2022 ) as determined by multiplex ELISA ( Fig. 7 F ).…”
Section: Resultsmentioning
confidence: 68%
“…Using both in vitro and in vivo approaches, the latter involving cell specific Hsp25 gene-targeted deletion and overexpression murine models, we report that Hsp25/27 is an essential facilitator of the transcription factor STAT3 (Signal transducer and activator of transcription 3) which functions to converge many cooperative gut microbial and host signals that promote intestinal mucosal restitution following immune and inflammatory stress and injury. STAT3 has been shown to control cell growth, division, migration, and apoptosis to proinflammatory actions and its phosphorylation and activation by IL-22 promotes mucosal healing [35][36][37][38][39][40][41] . Conversely, STAT3 is involved in pro-inflammatory cytokine signaling through the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway that is associated with autoimmune disorders and various cancers 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to T cells, ILC activity is not restricted to a specific antigen but does rely on the integration of environmental signals driving their effector functions ( Klose and Artis, 2020 ). Despite apparent redundancy, ILC and T cells play complementary roles with distinct temporal activity that enables them to eliminate pathogens and preserve tissue homeostasis ( Rankin et al., 2016 ; Serafini et al., 2022 ). Due to a significant overlap between T cell and ILC transcriptomic profiles ( Ercolano et al., 2020 ) and effector functions, it remains challenging to unravel the actions of individual genes regulators in ILC homeostasis through gene deletional targeting ( Cording et al., 2018 ).…”
Section: Before You Beginmentioning
confidence: 99%